Profil Total Bilirubin, Aktivitas Alanine Transaminase dan Total Protein Domba Garut pada Umur dan Status Fisiologis yang Berbeda - Sarmin, Sarmin; Astuti, Pudji; Airin, Claude Mona; Adianto, Nur (Jurnal Veteriner; Vol 23 No 3 (2022)DO - 10.19087/jveteriner.2022.23.3.432, 2022)
The purpose of this study was to examine the profiles of total bilirubin, ALT activity, and total protein in Garut sheep at different ages and physiological stasus.  A total of 36 head of Garut sheep with various physiological conditions (ewe, ram, female suckling lamb, male suckling lamb, female postweaning lamb, male postweaning lamb, young ram  aged six month, young ram aged one, pregnant ewe, and lactating ewe) was used in this research.  Blood samples were taken through the jugular vein in the morning before the sheep were fed. Then, the values of total bilirubin, alanine aminotransferase (ALT), and total protein were analyzed.  The mean total bilirubin value of Garut sheep was 0.59 ± 0.49 mg/dL, influenced by age and not affected by sex or physiological status. The total bilirubin value of ewe lambs was the highest (1.85 ± 0.87 mg/dL) compared to the total bilirubin value at other ages. The average value of ALT activity in garut sheep was 18.84 ± 6.56 U/L, which is influenced by age but not affected by physiological status or gender. The value of ALT activity in female suckling lamb was the lowest (7.03 ± 0.81 U/L) compared to ALT activity at other ages. The average total protein of Garut sheep was 6.48 ± 0.83 (g/dL), which was affected by age but not affected by sex or physiological status. The lowest total protein was found in female suckling lamb (.51 ± 0.59 g/dL) compared to total protein values at other ages. It was concluded that age affected the values of total bilirubin, ALT activity, and total protein in Garut sheep.  Therefore, the age of Garut sheep should be considered in the interpretation of total bilirubin, ALT activity, and total protein.